Enhancing the microstructure and mechanical properties of CrCoFeNiAl high-entropy alloy produced by hot press sintering through laser remelting - Xi Wang; Haodong Tian; Yuzhen Yu; Shuangyu Liu; He Liu; Ben Wang; Hanpeng Gao (Journal of Materials Research and Technology, 2024)
Herein, laser remelting (LR) and hot press sintering (HPS) were combined to process high-entropy alloy (HEA) and strengthen desirable microstructure. The microstructural changes of HEA before and after LR processing were experimentally investigated. In Scanning Electron Microscope (SEM) and electron backscatter diffraction (EBSD) observations, it was found that the microstructure of the remelting zone was mainly composed of dendritic isometric crystals, and the laser remelting technique can refine the grain structure of HEA. The combined strengthening features of dislocations and twinning were observed by Transmission electron microscopy (TEM), and the phase structure of the grains was analyzed in conjunction with the X-ray diffraction(XRD) analysis, confirming the presence of B2 with BCC solid-solution and FCC phase. Finally, micron-sized scratches, tensile experiments and microhardness experiments were performed, and it was found that the Mechanical properties of the remelting zone were significantly enhanced. It was demonstrated that the strengthening of HEA, sintered by LR and HPS techniques, is due to the synergistic influence of various strengthening mechanisms, such as fine grain strengthening, dislocation strengthening, solid-solution strengthening and twinning strengthening.